New English File. Upper-Intermediate: Woorkbook - Oxenden C. Clive (New York, Oxford University Press, 2010)
The course that gets students talkingFun, motivating lessons that work. The perfect balance of grammar, vocabulary, pronunciation, and skills to help your students use English really effectively. A complete package for teachers and students. The Teacher's Book gives you the support you need, and all the components work together for more effective learning. Common European Framework of Reference B2 Workbook. Lesson by lesson revision and practice. More Words to Learn - extra words from the Student's Book. Check what you know - grammar revision tables and exercises.Look out for the Study Link logo in the Workbook. This showsyou where to find more material for revision and practice.